Malaria and economic evaluation methods: Challenges and opportunities - Drake, T; Lubell, Y (Springer, 2017)
There is a growing evidence base on the cost effectiveness of malaria interventions. However, certain characteristics of malaria decision problems present a challenge to the application of healthcare economic evaluation methods. This paper identifies five such challenges. The complexities of i) declining incidence and cost effectiveness in the context of an elimination campaign ii) international aid and its effect on resource constraints and iii) supranational priority setting, all affect how health economists might use a cost effectiveness threshold. Consensus and guidance on how to determine and interpret cost effectiveness thresholds in the context of internationally financed elimination campaigns is greatly needed. iv) Malaria interventions are often complimentary and evaluations may need to construct intervention bundles to represent relevant policy positions as sets of mutually exclusive alternatives. v) Geographic targeting is a key aspect of malaria policy making that is only beginning to be addressed in economic evaluations. An approach to budget-based geographic resource allocation is described in an accompanying paper in this issue and addresses some of these methodological challenges.